Respon Perkecambahan Benih Jati Putih (Gmelina arborea Roxb.) Terhadap Perendaman Atonik - Sosimus Ado; Astin E. Mau; Norman P. L. B. Riwu Kaho (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
White teak (Gmelina arborea Roxb.) is one of type of plant that can be develop in the plantation forests, especially community forests. This type of exotic tree can grows quickly, ease to planting, and makes economic benefits. White teak wood can be used for light construction, crafts, home furnishing, matches, particle boards, containers, and woodworking. The application of atonic growth regulator (GRS) has the ability to accelerate germination, stimulate plant root growth, activation of nutrient absorption, promotes vegetative growth, and increase bud output. This study aims to determined the effects of atonic concentration on the germination of white teak seeds and to find out one of the atonic soaking treatments that has the best effect on the germination. The method used in this study was a Complete Random Design (RAL) with the comparison of the several atonic concentration that consist of (P0) without atonic / control, (P1) atonic 1 ml/L, (P2) atonic 1.5 ml/L, (P3) 2 ml/L. Each treatments were repeated 4 times so there were 16 experimental units that were obtained. Each experimental unit requires 10 white teak seeds, so the total of all treatments and replication requires the total of 160 white teak seeds. The results showed that the atonic concentration had a very significant effect on germination ability and germination speed index. Also, it has significant effect on the germination value of white teak plants. The effect of atonic concentration of P2 treatment (1.5 ml/L) was the best treatment that affected germination ability, germination speed index, and germination value of white teak plants. At this concentration the plant can germinate well compared to the other treatments.